Primary Grade Children’s Capacity to Understand Microevolution: The Power of Leveraging Their Fruitful Intuitions and Engagement in Scientific Practices - Metz, Kathleen Emlen; Cardace, Amy; Berson, Eric; Ly, Uyen; Wong, Nicole; Sisk-Hilton, Stephanie; Metz, S. Emlen; Wilson, Mark (Journal of the Learning Sciences, 2019)
We investigated second and third graders’ capacity to understand microevolution, given a learning progression leveraging intuitions to build more adequate explanations, problematizing core ideas within scientific practices, and in-depth study of a single domain (botany or animal behavior). The intervention was implemented in both researcher-taught summer school and regular school-year classrooms in two consecutive years, allowing refinement of instruction mid-course, as well as comparison of learning outcomes. A case study examined how the pedagogy functioned within a strategically selected segment of curriculum enactment. Analysis of pre- and post-instruction interviews, using mean scaled estimates and maximum learning progression levels, revealed significant conceptual advancements for all cohorts across both sites and years. After Year I, a majority of children in researcher-taught and regular classrooms could predict and explain the impact of traits’ differential survival advantage on next-generation shifts in relative frequency given particular environmental change. After Year II, the majority in each cohort formed normative predictions and explanations of population changes across multiple generations. This pattern reflects a basic understanding of microevolution, providing evidence of the capacity of primary grade children to understand abstract ideas and, more generally, to benefit from much more conceptually and epistemically ambitious curriculum than current science standards recommend.